PERAN ORANG TUA DALAM PROSES BELAJAR ANAK DI MASA PANDEMI COVID-19 DALAM MENUMBUHKAN SIKAP ILMIAH (Studi Kasus Pada Siswa Usia 10-12 Tahun pada Mata Pelajaran IPA) - Ardiansyah, Ardiansyah; Arda, Arda (Musawa: Journal for Gender Studies, 2020)
The purpose of this study was to identify the role of parents in fostering children's scientific attitudes in science lessons in the midst of the pandemic situation COVID-19. The method used in this research is a case study, namely the research design used to reveal in more detail and comprehensively the situation of the object being analyzed. In addition, researchers also use qualitative case study methods used to obtain information. The results showed that the planning of planting scientific attitudes by parents was to provide opportunities for children to demonstrate scientific attitudes. The implementation of planting scientific attitudes by showing examples of scientific attitudes, providing positive reinforcement or rewards for students who show scientific attitudes, and providing opportunities for students to show scientific attitudes. The attitudes shown in the indicators of scientific attitudes studied, namely the attitude of curiosity, objective attitudes towards data and sensitive attitudes towards the environment are included in the high quality category in this study. by: (a). the ability of parents who are not sufficient in guiding / accompanying their children to study at home, especially in material that involves the experimental process in the learning process, (b). The teacher's explanation time in online learning is considered by parents to be very short which results in confusion in accompanying children to study at home, (c). inadequate facilities and infrastructure.